Pemetaan Daerah Rawan Bencana Banjir Di Kecamatan Kwandang Kabupaten Gorontalo Utara Provinsi Gorontalo - Saleh, Cindra; Rusiyah, Rusiyah; Pambudi, Moch Rio (Universitas Negeri Gorontalo, 2026)
This study aims to develop a detailed and accurate flood vulnerability map to support local governments, the Regional Disaster Management Agency (BPBD), and other stakeholders in designing effective structural and non-structural flood mitigation strategies in North Gorontalo Regency, Indonesia. A quantitative approach employing spatial descriptive analysis was applied to assess flood vulnerability based on key physical and environmental parameters. Geospatial data constituted the primary basis of analysis and were processed using Geographic Information Systems (GIS) to generate spatially explicit vulnerability maps. Data were obtained from secondary sources, complemented by field observations and documentation studies. The results indicate that flood vulnerability in the study area is predominantly classified as moderate to high. Quantitatively, slightly vulnerable areas account for 28.76% of the total area, followed by moderately vulnerable areas at 28.23% and vulnerable areas at 24.48%. Very vulnerable areas cover 16.41%, while non-vulnerable areas represent only 2.11%. Spatial analysis reveals that villages located in low-lying areas, in close proximity to river channels, and characterized by gentle slope gradients exhibit the highest levels of flood vulnerability. Notably, Alatakarya, Upper Pontolo, Molingkapoto, and Katialada villages consistently fall within the vulnerable to very vulnerable categories. Overall, this study provides critical insights into flood vulnerability levels, spatial distribution patterns, and the identification of priority villages, underscoring the urgent need for targeted mitigation measures in areas with the highest flood risk.